ANALISIS KEBANGKRUTAN ALTMAN Z-SCORE MODIFIKASI PT BLUE BIRD TBK - Waldani, Anggi Jumiafitri; Aulia, Putri; Nurlinda (Jurnal Budgeting, 2023)
This study aims to analyze the financial condition of the Blue Bird Tbk company for 2018 - 2022 using the Altman Z-Score Bankruptcy Prediction Analysis with a modified formula. The data analyzed is secondary data in the form of company financial report data for 2018 - 2022. The type of research used is descriptive research with a quantitative approach and documentation data collection. The research results show that in the Modified Altman Z-Score, PT Blue Bird Tbk for 2018 - 2022 is predicted to be Non Financial Distress, this indicates that there are no financial difficulties faced by the company.